Rare lymphomas in routine practice—Treatment and outcome in Waldenström's macroglobulinaemia in the prospective German Tumour Registry Lymphatic Neoplasms. Issue 3 (8th May 2020) - Knauf, Wolfgang; Abenhardt, Wolfgang; Slawik, Hans Rainer; Bückner, Ute; Otremba, Burkhard; Sauer, Annette; Zahn, Mark‐Oliver; Wetzel, Natalie; Kaiser‐Osterhues, Anja; Houet, Leonora; Marschner, Norbert; ,
Abstract: Waldenström's macroglobulinaemia (WM) is a rare indolent B‐cell lymphoma for which only little prospective phase III evidence exists. Thus, real world data are important to provide insight into treatment and survival. We present here data on choice and outcome of systemic treatment of patients with WM treated in German routine practice. In total, 139 patients with WM who had been documented in the prospective clinical cohort study Tumour Registry Lymphatic Neoplasms (NCT00889798) were included into this analysis. We analysed the most frequently used first‐line and second‐line treatments between 2009 and 2017 and examined best response, progression‐free survival (PFS) and overall survival (OS). Bendamustine plus rituximab, with a median of six cycles, was by far the most frequently used first‐line treatment (81%). Second‐line treatment was more heterogenous and mainly based on bendamustine, cyclophosphamide/doxorubicin/vincristine/prednisone (CHOP), fludarabine or ibrutinib, the latter approved in 2014. Three‐year PFS from start of first‐line treatment was 83% (95% confidence interval [CI] 74%‐88%), 3‐year OS was 87% (95% CI 80%‐92%). These prospective data give valuable insights into the management and outcome of non‐selected patients with WM treated in German routine practice. In the lack of prospective phase III clinical trials, real world data can help bridging the gap of evidence.